The Role of Financial Technology in Personal Financial Planning for the Millennial Generation in Urban Indonesia Today - Ratnawati, Dwi Puji; Pratiwi, Rifka Sari; Rukmana, Indra Heri (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The rapid advancement of financial technology (fintech) has significantly reshaped how millennials in urban Indonesia manage their personal finances. Characterized by high digital literacy and mobile dependence, this generation has increasingly adopted fintech platforms for budgeting, saving, investing, and accessing financial protection. This study aims to analyze the role of fintech in supporting the personal financial planning of urban millennials, focusing on four key dimensions: cash flow management, savings, investment behavior, and financial protection. Using a qualitative approach with a literature review method, data were collected from ten peer-reviewed articles published between 2018 and 2025. The selected literature was analyzed thematically to identify patterns and synthesize insights. The findings reveal that fintech tools have facilitated more organized financial behaviors among millennials, enabling automation in savings, simplified investment access, and enhanced budgeting control. Moreover, fintech has played a vital role in democratizing access to insurance products. However, the study also found that the effectiveness of fintech is contingent upon the users’ level of financial literacy. While many millennials are eager to adopt digital financial solutions, gaps remain in risk awareness, long-term planning, and responsible consumption. Therefore, although fintech has the potential to transform financial planning, its benefits are maximized when accompanied by adequate financial education.